1993
DOI: 10.1126/science.8266099
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Condensation in Xenopus Mitotic Extracts Without Histone H1

Abstract: The contribution of histone H1 to mitotic chromosome condensation was examined with the use of a cell-free extract from Xenopus eggs, which transforms condensed sperm nuclei into metaphase chromosomes. When H1 was removed from the extract, the resultant metaphase chromosomes were indistinguishable from those formed in complete extract. Nucleosomal spacing was the same for both. Thus, H1 is not required for the structural reorganization that leads to condensed metaphase chromosomes in this egg extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 36 publications
10
93
1
Order By: Relevance
“…It has been much easier to establish some of the things that these H1 variants do not do during early embryonic development. Depletion of B4 from Xenopus oocyte extracts, for instance, has demonstrated that the presence of this histone is not required for the assembly of morphologically normal pronuclei which are capable of DNA replication (Ohsumi et al, 1993;Dasso et al, 1994). Similar experiments also established that B4 did not contribute to the physiological spacing of nucleosomes .…”
Section: Fertilizationsupporting
confidence: 51%
“…It has been much easier to establish some of the things that these H1 variants do not do during early embryonic development. Depletion of B4 from Xenopus oocyte extracts, for instance, has demonstrated that the presence of this histone is not required for the assembly of morphologically normal pronuclei which are capable of DNA replication (Ohsumi et al, 1993;Dasso et al, 1994). Similar experiments also established that B4 did not contribute to the physiological spacing of nucleosomes .…”
Section: Fertilizationsupporting
confidence: 51%
“…As shown in previous studies (23,34), extensive nuclease digestion of B4-free nucleosomes, i.e., nucleosome cores, produced a DNA fragment of 146 bp (Fig. 2H, lane 2), which was protected by the core histones alone, whereas nuclease digestion of nucleosomes containing B4 produced a DNA fragment of Ϸ170 bp (Fig.…”
Section: Involvement Of Nap-1 In Nucleosome Assembly Of Sperm Chromatmentioning
confidence: 97%
“…Demembranated Xenopus sperm prepared as described (23) was incubated with egg extract and histidine-tagged p60 xNAP-1 (His-xNAP-1) solutions at a final concentration of 5,000͞ l. After 30-min incubation, sperm chromatin was sedimented onto a sucrose cushion by centrifugation and examined for linker histone binding. SDS͞PAGE of acidextracted proteins and micrococcal nuclease digestion assay were performed as described (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of histone H1 during entrance of cell to mitosis was reported over three decades ago (5), and the role of this modification in chromatin condensation has been postulated (6). More recent studies, however, have shown that histone H1 is not required for chromatin to undergo mitotic condensation (7,8).…”
mentioning
confidence: 99%